How to explore dancers` sense experiences? A study of how multi-sited fieldwork and phenomenology can be combined - Ravn, S.; Ploug Hansen, H. (Qualitative Research in Sport, Exercise and Health, 2013)
In this article, we deal with how sense experiences can be described and analysed in movement activities such as dance. We present a methodological framework of how multi-sited fieldwork and phenomenology can be combined to explore ongoing constitutive processes of subjects` sense experiences. The challenge of how to employ phenomenology in relation to a fieldwork based on particular and subjective experiences is constructively related to phenomenological discussions of the content versus the structure of experience. Phenomenology as a philosophical enterprise is subsequently linked to concrete methodological challenges, by presenting and discussing how, in a specific study, we handle the `in practise` sense experiences of different dancers. Being a dancer herself, the first author included her embodied competence when performing the fieldwork. The body thereby became both the researcher`s tool and the subject to be investigated. The comparative structure implicit to performing a multi-sited fieldwork was used to build a creative tension between the researcher`s and the dancers` experiences. Two descriptions of dancers` sense experiences are presented. They exemplify how the dancers turn to an overall sense of how the body feels in preference to working with specific modalities of sensing. Furthermore, the dancers` sensing of the physicality of their moving bodies appears to be shaped by their unique intention is at the same time given form through their interactions with other dancers.